Financial leverage and its influence on the profitability of companies, period 2008-2017 - Casamayou Calderón, Elisabeth Teresa (2019)
Objective: The main objective of this research was to determine the influence of financial leverage on the profitability of companies belonging to the industrial sector that are listed on the Lima stock exchange in the 2008-2017 period. Method: The type of study is non-experimental because the variables were not manipulated and it is quantitative by the numerical data that we have used in the research.  The research design is longitudinal. Thirty-four companies were analyzed, using panel-type data for simultaneous analysis over a period of 10 years; finally, the level of research is descriptive, correlational and causal, due to the direct relationship between the study variables. Results: It was found that financial leverage has a significant influence on profitability, that explains it at 21.85%, it also influences the share price (23.18%). The operating margin and operating expenses did not influence the profitability in isolation. In the simultaneous analysis, financial leverage and operating margin significantly influenced the profitability of the study companies that explained it at 23.56%. Conclusions: It was concluded that financial leverage influences less than 50% in profitability. This indicates that there are other variables that explain its behavior such as share price, operating margin and operating expenses, which were taken into account in the investigation.